Canva Training by Teaching Campus Students in Developing Digital Literacy Skills in Educational Environments - Nurhayati, Nurhayati; Lasmi, Hardiyanti; Fujiastuti, Winarni; Hasanah, Niswayanti; Jumrah, Jumrah; Permatasari, Mita (Journal of Universal Community Empowerment Provision, 2024)
Training in using the Canva application is one of the most important things in developing digital literacy skills in the educational environment because Canva as a technology-based application provides a learning space for every educator and student to carry out learning. The aim of this activity is to improve participants' abilities in creating learning media and educational posters using Canva. The method used in this training activity is qualitative through descriptive analysis techniques. The training was carried out by providing material and direct practice using the Canva application. This activity was attended by 66 participants who were educators and students from three schools in different locations. The research results showed that Canva training provided participants with a positive experience in developing their digital literacy skills. Participants expressed an increase in their deeper understanding of graphic design and creating visual learning materials after participating in this activity.